Carbon–chalcogen bond formation initiated by [Al(NONDipp)(E)]− anions containing Al–E16 (E16 = S, Se) multiple bonds. Issue 16 (7th April 2022) - Evans, Matthew J.; Anker, Mathew D.; McMullin, Claire L.; Neale, Samuel E.; Rajabi, Nasir A.; Coles, Martyn P.
Abstract : Reaction of Al–E (E = S, Se) multiple bonds with C{O functionalities generates new C–E bonds. Abstract : Multiply-bonded main group metal compounds are of interest as a new class of reactive species able to activate and functionalize a wide range of substrates. The aluminium sulfido compound K[Al(NON Dipp )(S)] (NON Dipp = [O(SiMe2 NDipp)2 ] 2−, Dipp = 2, 6- i Pr2 C6 H3 ), completing the series of [Al(NON Dipp )(E)] − anions containing Al–E16 multiple bonds (E16 = O, S, Se, Te), was accessed via desulfurisation of K[Al(NON Dipp )(S4 )] using triphenylphosphane. The crystal structure showed a tetrameric aggregate joined by multiple K⋯S and K⋯π(arene) interactions that were disrupted by the addition of 2.2.2-cryptand to form the separated ion pair, [K(2.2.2-crypt)][Al(NON Dipp )(S)]. Analysis of the anion using density functional theory (DFT) confirmed multiple-bond character in the Al–S group. The reaction of the sulfido and selenido anions K[Al(NON Dipp )(E)] (E = S, Se) with CO2 afforded K[Al(NON Dipp )(κ 2 E, O -ECOO)] containing the thio- and seleno-carbonate groups respectively, consistent with a [2 + 2]-cycloaddition reaction and C–E bond formation. An analogous cycloaddition reaction took place with benzophenone affording compounds containing the diphenylsulfido- and diphenylselenido-methanolate ligands, [κ 2 E, O -ECOPh2 ] 2− . In contrast, when K[Al(NON Dipp )(E)] (E = S, Se) was reacted with benzaldehyde, two equivalents of substrate were incorporated into the product accompanied by formation of a second C–E bond and complete cleavage of the Al–E16 bonds. The products contained the hitherto unknown κ 2 O, O -thio- and κ 2 O, O -seleno-bis(phenylmethanolate) ligands, which were exclusively isolated as the cis -stereoisomers. The mechanisms of these cycloaddition reactions were investigated using DFT methods.